2022
DOI: 10.1590/1807-3107bor-2022.vol36.0106
|View full text |Cite
|
Sign up to set email alerts
|

The effect of socioeconomic aspects and dental history on pediatric patients’ dental anxiety

Abstract: Edson Paiva PEREIRA JUNIOR (b) Raildo da Silva COQUEIRO (b) Andréa FONSECA-GONÇALVES (a) Lucianne Cople MAIA (a) Matheus Melo PITHON (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Goettems et al [17], who investigated the relationship between the influence of maternal dental anxiety, the pattern of dental check-up utilization and the child's perception of quality of life, found that children in Brazil from families with a higher socioeconomic status were five times more likely to have used dental health services than children with a lower economic status. Previous studies have suggested that socioeconomic status may be a key factor in dental anxiety, with children from the lowest socioeconomic groups showing higher levels of dental anxiety [18]. This suggests that socioeconomic status may be a key factor in dental anxiety.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Goettems et al [17], who investigated the relationship between the influence of maternal dental anxiety, the pattern of dental check-up utilization and the child's perception of quality of life, found that children in Brazil from families with a higher socioeconomic status were five times more likely to have used dental health services than children with a lower economic status. Previous studies have suggested that socioeconomic status may be a key factor in dental anxiety, with children from the lowest socioeconomic groups showing higher levels of dental anxiety [18]. This suggests that socioeconomic status may be a key factor in dental anxiety.…”
Section: Introductionmentioning
confidence: 93%
“…This suggests that socioeconomic status may be a key factor in dental anxiety. However, this was not observed in the results of Amorim et al [18]. Ramseier et al [19] investigated the relationship between socioeconomic factors and dental anxiety in a group of 2240 participants aged 43.5 ± 16.0 years and found a statistically significant inverse relationship: a higher level of education correlated with a lower level of dental anxiety.…”
Section: Introductionmentioning
confidence: 93%